2013
DOI: 10.1242/jeb.096347
|View full text |Cite
|
Sign up to set email alerts
|

Rhodopsin coexpression in UV photoreceptors of Aedes aegypti and Anopheles gambiae mosquitoes

Abstract: Differential rhodopsin gene expression within specialized R7 photoreceptor cells divides the retinas of Aedes aegypti and Anopheles gambiae mosquitoes into distinct domains. The two species express the rhodopsin orthologs Aaop8 and Agop8, respectively, in a large subset of these R7 photoreceptors that function as ultraviolet receptors. We show here that a divergent subfamily of mosquito rhodopsins, Aaop10 and Agop10, is coexpressed in these R7 photoreceptors. The properties of the A. aegypti Aaop8 and Aaop10 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…Unlike its distant cousin Drosophila , Aedes aegypti PRs form a fused rhabdom, and express at least five Rhodopsins (Figure 5E). Recent investigation of the retinal mosaic from Aedes revealed several surprising findings [100102]: First, there is no apparent stochastic mosaic of ommatidial subtypes, based on Rhodopsin expression in R7 cells. Secondly, the four R7 Rhodopsins (UV, Blue, 2× long-wavelength/Green) are always co-expressed, yet in different combinations, between different regions of the eye.…”
Section: Emerging Design Challenges: Retinal Bands and Stripesmentioning
confidence: 99%
“…Unlike its distant cousin Drosophila , Aedes aegypti PRs form a fused rhabdom, and express at least five Rhodopsins (Figure 5E). Recent investigation of the retinal mosaic from Aedes revealed several surprising findings [100102]: First, there is no apparent stochastic mosaic of ommatidial subtypes, based on Rhodopsin expression in R7 cells. Secondly, the four R7 Rhodopsins (UV, Blue, 2× long-wavelength/Green) are always co-expressed, yet in different combinations, between different regions of the eye.…”
Section: Emerging Design Challenges: Retinal Bands and Stripesmentioning
confidence: 99%
“…Therefore only the activity of Aaop7 or the Rh1 control rhodopsin was represented in the ERG response (Ahmad et al, 2006). The Aaop7-and the Rh1-expressing Drosophila were then subjected to ERG analysis as described previously (Hu et al, 2014). Narrow band pass and neutral density filters (Oriel, Stratford, CT) were used to attenuate a 1000 W tungsten light source (Oriel, Irvine, CA) so that the flies could be exposed to light stimuli of comparable photon content (20 μE m −2 s −1…”
Section: Spectral Analysis By Erg Recordingsmentioning
confidence: 99%
“…Three of these groups are labeled as long-wavelength (>500 nm), short-wavelength (400-500 nm), and UV-sensitive rhodopsin (<400 nm), and two of these groups contain uncharacterized family members. We previously characterized the patterns of rhodopsin expression in the adult Aedes compound eye (Hu et al, 2009(Hu et al, , 2011(Hu et al, , 2012(Hu et al, , 2014. These studies revealed features of the visual system in Aedes that were not predicted from study of other invertebrate models.…”
Section: Introductionmentioning
confidence: 99%
“…In these instances opsin co-expression is thought to broaden the spectral sensitivity of the photoreceptor. A number of examples come from insect photoreceptors (Kitamoto et al, 1998;Arikawa et al, 2003;SisonMangus et al, 2006;Mazzoni et al, 2008;Hu et al, 2014). The small VE photoreceptors in Limulus provide another example.…”
Section: The Three Visible Light-sensitive Opsins In Limulus Mes Are mentioning
confidence: 99%